Bloom of Trichodesmium (Oscillatoriales, Phormidiaceae) and seasonality of potentially harmful phytoplankton in San Pedro Bay, Leyte, Philippines - Yap-Dejeto, Leni G.; Batula, Haide S. (Revista de Biología Tropical, 2016)
Since 1983, San Pedro Bay in the Philippines had been reported to be the site of episodic Pyrodinium bahamense var. compressum blooms that caused paralytic shellfish poisoning in its nearby coastal communities. This bay is also subjected to numerous storms; the strongest was super typhoon Haiyan in November 8, 2013. For the first time, the seasonal dynamics of potentially toxic and harmful phytoplankton in this bay is elucidated. This is also the first record of a bloom of the cyanobacteria, Trichodesmium erythraeum that reached 70 000 colonies/L in April 2013 in this area. There were other 19 potentially toxic and harmful phytoplankton encountered during the sampling period. These consisted of a haptophyte, Phaeocystis globosa, the diatom Pseudo-nitzschia and 17 dinoflagellates. Seven of these harmful algae had densities high enough to be traced through time. Normally, diatoms abound during the dry season. But Pseudo-nitzschia increased in abundance during the wet season of 2012 and 2013. The dinoflagellates and Phaeocystis globosa behaved as expected and exhibited a relative increase in cell density during the rainy season of both years too. High nutrient availability during this season must have influenced the behavior of the phytoplankton despite differences in temperature and light intensity among seasons. Other notable but rare harmful species found only in plankton net tows during the study were Pyrodinium bahamense var. compressum, Alexandrium tamiyavanichii, Cochlodinium polykrikoides, and Noctiluca scintillans.